Resolution of Inheritance Disputes in Gayo Society through Mediation: Perspective of Welfare and Gender Justice - Bustami, Kasdim; Saleh, Fauzi; Nurdin, Ridwan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The resolution of inheritance disputes in the Gayo Lues community, where women are disadvantaged (discriminated against) or receive injustice in the distribution of inheritance, leads to conflicts, disputes, and hostility within the family, causing disharmony within the family, society, culture, and customs. As a result, women in the Gayo Lues community do not fully receive their inheritance rights. Dispute resolution outside the court is called alternative dispute resolution (ADR). This research was conducted in Gayo Lues Regency, using a descriptive qualitative approach. The policy and implementation of mediation in resolving inheritance disputes are carried out through family deliberation, as the goal of "beredet" (family deliberation) is "dame" or "mupakat jeroh" (peace or mutual agreement). In resolving and dividing inheritance in the Gayo Lues community, women do not participate at all and do not receive any part of the inheritance. Women face obstacles in reaching their maximum potential due to gender injustice and inequality. The concept pursued in resolving inheritance disputes between men and women in the Gayo Lues community includes "mupakat jeroh" (deliberation), "timang rasa" (sense of justice), and peaceful means ("dame").